Cell cycle-dependent binding between Cyclin B1 and Cdk1 revealed by time-resolved fluorescence correlation spectroscopy. Issue 6 (29th June 2022) - Barbiero, Martina; Cirillo, Luca; Veerapathiran, Sapthaswaran; Coates, Catherine; Ruffilli, Camilla; Pines, Jonathon
Abstract : Abstract : Measuring the dynamics with which the regulatory complexes assemble and disassemble is a crucial barrier to our understanding of how the cell cycle is controlled that until now has been difficult to address. This considerable gap in our understanding is due to the difficulty of reconciling biochemical assays with single cell-based techniques, but recent advances in microscopy and gene editing techniques now enable the measurement of the kinetics of protein–protein interaction in living cells. Here, we apply fluorescence correlation spectroscopy and fluorescence cross-correlation spectroscopy to study the dynamics of the cell cycle machinery, beginning with Cyclin B1 and its binding to its partner kinase Cdk1 that together form the major mitotic kinase. Although Cyclin B1 and Cdk1 are known to bind with high affinity, our results reveal that in living cells there is a pool of Cyclin B1 that is not bound to Cdk1. Furthermore, we provide evidence that the affinity of Cyclin B1 for Cdk1 increases during the cell cycle, indicating that the assembly of the complex is a regulated step. Our work lays the groundwork for studying the kinetics of protein complex assembly and disassembly during the cell cycle in living cells.